Queen of the Night : Walker Family #4 - Jance, Judith A. (New York : William Morrow, 2010)
Murders old and new disturb the peace of Tohono O'odham Nation residents and their Arizona neighbors in this fourth entry in Jance's Walker Family series. Californian Jonathan Southard is so seething with resentment that he kills his wife and children and goes after his remarried mother in Tucson. Reverberations from Southard's crimes touch the former sheriff Brandon Walker, his wife, Diana, and their adopted Native American daughter, Lani, exacerbating old wounds at a time when Walker is worried about Diana's mental health. Perhaps as a way of reacquainting readers with this seriesthere have been lapses of three to four years between installmentsJance inserts great chunks of backstory, as Diana hallucinates dead men who once terrorized her. Tohono O'odham tales and culture, which permeate the book (reminiscent of Tony Hillerman), and the flower of the title, the beautiful and aromatic cereus, which blooms in the desert just one night each year, add appeal, but the awkward backstorry gimmick and the lack of much narrative pulse make this a somewhat tepid entry from a best-selling author.
Keywords: Cold cases (Criminal investigation) -- Fiction; Arizona -- Fiction; Mystery fiction